Designing Knowledge Based Performance Management System (KBPMS) in Coffindo Bandung Branch - Pasaribu, Amanah; Wibisono, Dermawan (The Indonesian Journal of Business Administration, 2016)
Abstract- Coffindo is known as one of coffee company in Indonesia and has been established since 1999. The company has grown into a national export and trading company and has 9 sales offices in Medan, Jakarta, Surabaya, Pekanbaru, Bali, Bandung, Balikpapan, Singapore and United State of America. On Coffindo Bandung branch, the business sector focused on supply company product to market trade, hotel restaurant cafe (horeca) and coffee shop. The current competitive conditions occur very quickly. The company is expected to improve the performance of external and internal in order to realize the vision. The critical issue is because the company does not have a performance management system. This study was conducted to design performance management system in the Coffindo Bandung branch. Proposed the Knowledge-Based Performance Management System (KBPMS) as the framework considers that KBPMS allows measure performance in integrated ways. The method of collecting data uses interview and distribute questionnaires to the manager and employees of the company. To determine the indicator linkage was used Analytical Hierarchy Process (AHP).  KBPMS has three perspectives include business result, internal process and resource capability perspective. In this study business result perspective includes finance aspect of 3 measurement indicators and financial aspect of 3 measurement indicators. Internal process perspective includes innovation aspect of 2 measurement indicators, operation aspect of 3 measurement indicators and marketing aspect of 3 measurement indicators. Resource capability perspective have 4 measurement indicators include human resource, technology resource and organizational resource. The finding of linkage using AHP shows that finance is more important than non financial and sales growth affected it. For internal process the value of priority vector average for innovation is higher than the operation and marketing, and the product innovation indicators affected it. Human resource is the important indicators for resource capability.  Benchmark describe that Coffindo lag behind in support and market share in the segment of Horeca. Finally, this designing performance management system needs to be implemented and the implementation plan consists of measurement, evaluation, diagnosis and follow up.   Keywords: Coffindo, Knowledge-based performance management system (KBPMS), analytical hierarchy process (AHP), Benchmark